Prosorhynchus Odhner, 1905 (Digenea: Bucephalidae) from the orange-spotted grouper Epinephelus coioides (Hamilton, 1822) (Epinephelidae), including Prosorhynchus tonkinensis n. sp., from the Gulf of Tonkin, Vietnam - Truong, Thuong Van; Palm, Harry W.; Bui, Te Quang; Ngo, Huong Thi Thuy; Bray, Rodney A. (Zootaxa, 2016)
A total of 169 specimens of the orange-spotted grouper Epinephelus coioides (Hamilton) were collected from fishermen and marine fish farms in the Gulf of Tonkin, Vietnam. Five different species of Prosorhynchus Odhner, 1905 were recorded, including P. tonkinensis n. sp. The new species differs from all other Prosorhynchus species in the presence of an indented posterior extremity. It can be distinguished from the most closely related P. atlanticus Manter, 1940 and P. crucibulum Rudolphi, 1819 by the extension of the uterus always to the level of the ovary, the width and premouth distance in the former, and the arched vitellarium and smaller egg size in the latter, and a different host and geographical region. Prosorhynchus sp. A (not fully identified in this study) has been earlier reported from E. coioides from New Caledonia (see Prosorhynchus sp. B of Bray and Justine, 2013), P. luzonicus Velasquez, 1959 is reported throughout South-East Asia, and Prosorhynchus sp. B (no further identification possible based on a single specimen in this study) and P. maternus Bray & Justine, 2006 are reported for the first time from Vietnam. The present study demonstrates a close relationship of the Prosorhynchus species composition in Vietnam with the Indo-Australian region, warranting further comparative studies among the different epinephelids.